Десять пуль на сундук мертвеца - Леонов Николай Иванович (Черная кошка, 2015)
Экземпляры: ф. 19 (20150929) / Инвентарный номер: 60044 / Цена: 231.00 / Авт.знак: Л 47 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6